(untitled) (Economic and Political Thought, 2014)
The article presents the role of the external influence on the development of Japan. Three historical periods essential for the process are emphasised. The first one was the Japanese adoption of Chinese solutions between the 7th and the 9th century. The second one was the turn of the 19th and the 20th century when Japan, after the so-called Meiji reform (1868), chose the path of modernisation spying western patterns out and following them. Finally, the last one was the period of reform during the American occupation of Japan after World War II (1945–1952) as well as a thoughtful adaptation of selected solutions of the Western civilization in a few next decades.